The Effect of Elastic Stiffness on the Shock Wave Propagation in Sandwich Structures: A Theoretical Analysis - Yu, Xuehui; Wang, Anshuai; Yang, Yan (Mechanics of solids, 2023)
Cellular materials have great potential in blast-mitigation engineering. Subject to an intensive load, cellular materials are damaged progressively and dissipates quantities of energy. In engineering applications, cellular materials are often used as the core of sandwich structures. In this article, we investigate the crushing of cellular core under impulsive loads theoretically. The supporting stiffness is considered and its effect on the propagation of plastic shock wave is addressed. Using the free-body diagram for sandwich structures, we distinguish three shock modes in the process of core crushing: single shock mode, single-single shock mode and single-double shock mode. Based on the R-PP-L material model, we give the governing equations for the three shock modes. It is hoped that the work in this article could give engineers some insights into the dynamic deformation of sandwich structures.